Mediating space: Framing strategy and sense of presence across the real-virtual environments - Ferro Yudistira; Ratu Baina (ARSNET, 2022)
This study discusses the idea of mediated space as a space formed through the combination of actor and entities in real and virtual environment. This mix of real and virtual environments is made possible through the involvement of the screen as the technological device that mediate the connection between them. Question then arises regarding the process that happen during this mediation, specifically regarding how to frame the virtual environment on the screen to establish an engagement with actor in real environment. Using the case of video game titled Persona 5, this study investigates this question through the concept of framing strategy and sense of presence. The discussion addresses two main points: (1) Utilisation of different framing strategies—based on the idea of immersion, mapping, and miniaturisation—provide different possibilities of action and interaction for the actor; (2) each framing strategy contribute to different dimension of presence that can complement each other within the formation process of mediated space.